Financial inclusion in Indonesia: data visualization and forecasting approach - Lacheheb, Zakaria; Lacheheb, Miloud (Empirical Economics Letters (EEL), 2023)
This study investigates the spread of financial inclusion in Indonesians’ islands namely; Sumatera, Jawa, Bali and Nusa Tenggara and Kalimantan. This study focuses on physical and digital financial inclusion based on their spread per Kilometer square and per adults. The method applied is Neural Network used for visualization and forecasting on 30 months ahead. The results indicate that Jawa has higher financial services compared with other islands, while Kalimantan recorded at lowest. The forecasting results indicate that, there is optimistic increase in the financial services in Indonesia but it is more on physical financial inclusion compared with the digital one.